Ultrasonic, Volumetric and Viscometric Studies of Monochloroacetic Acid Water-Isopropanol Solvent Mixtures at 25, 30 and 35 ºC - Nikam, P.S.; Hasan, Mehdi; Hiray, A.R. (Asian Journal of Chemistry, 2012)
Ultrasonic velocity, density and viscosity of monochloroacetic acid (MCAA) solutions in 10, 30, 50, 70, 90 and 100 wt. % isopropanol-water have been determined at 298.15, 303.15 and 308.15k. Viscosity and density data of these solutions are analysed with Jones-Dole and Masson equations respectively. The viscosity coefficients A and B, the limiting apparent molar volume (фov) and experimental slope (Sk), ultrasonic velocity (U) and derived parameters, namely adiabatic compressibility (βad), apparent molar compressibility (фk), intermolecular free length (Lf), specific acoustic impedance (z) and solvation number (Sn) through light on the solute-solvent and solute-solute interactions. Effect of temperature variation on these interactions is discussed.